Designing the impact pattern of electronic service quality through perceived value and electronic trust on customers' electronic commitment (case study of customers of different branches of Mellat bank in Shiraz). (2015) - Saneian, Z.; Seify, M.; Joukar, A.
The aim of the present study is to investigate and design the impact pattern of electronic service through perceived value and the customers' trust in the banking industry. The research sample population consists of all the customers of different branches of Mellat Bank in Shiraz, Iran. According to the analysis of structural equations, out of this sample population, 383 customers of different branches of the Bank were randomly selected. Its validity was accepted and its reliability was approved through Cronbach's Alpha with the value of 0.92. In order to conduct a research data analysis, structural equation modelling technique was applied through software Amos20. The results indicated that electronic service quality and its aspects have a positive and significant effect on the perceived value but a negative effect on electronic trust and also electronic trust has a positive effect on electronic commitment while, perceived value has a negative effect on electronic commitment.